Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
fcfgđsfđ

Giair Bất Phương Trình

\(\dfrac{x-1}{4}\)>\(\dfrac{x+2}{3}\)+\(\dfrac{x}{6}\)

Nguyễn Lê Phước Thịnh
2 tháng 5 2024 lúc 20:49

\(\dfrac{x-1}{4}>\dfrac{x+2}{3}+\dfrac{x}{6}\)

=>\(\dfrac{3x-3}{12}>\dfrac{4x+8}{12}+\dfrac{2x}{12}\)

=>3x-3>6x+8

=>-3x>11

=>\(x< -\dfrac{11}{3}\)


Các câu hỏi tương tự
Nguyễn Huy Tú
Xem chi tiết
8/5_06 Trương Võ Đức Duy
Xem chi tiết
Ha Pham
Xem chi tiết
Phạm Tiến Mạnh
Xem chi tiết
hiển nguyễn văn
Xem chi tiết
Mèo Dương
Xem chi tiết
Nguyễn Duy Khang
Xem chi tiết
Phạm Tiến Mạnh
Xem chi tiết
Hà Anh Chi
Xem chi tiết
Nhi Quỳnh
Xem chi tiết